Device identification using active noise interrogation and RF-DNA "fingerprinting" for non-destructive amplifier acceptance testing - Lukacs, Mathew; Collins, Peter; Temple, Michael (2016 IEEE 17th Annual Wireless and Microwave Technology Conference (WAMICON), 2016)
The cost of quality is critical to all industrial processes including microwave device production, which is often labor intensive and subject to production defects. Early defect detection can improve quality and reduce cost. A novel approach to defect detection has been demonstrated using a random noise radar (RNR), coupled with Radio Frequency Distinctive Native Attributes (RF-DNA) fingerprinting processing algorithms to non-destructively interrogate microwave devices. The RNR is uniquely suitable since it uses an Ultra Wideband (UWB) noise waveform as an active interrogation method that will not cause damage to sensitive microwave components and multiple RNRs can operate simultaneously in close proximity, allowing for significant parallelization of defect detection systems. Previous experimentation has demonstrated the ability to discern antenna loads and fault conditions, and identify faulty elements in a phased array antenna. This paper extends this method into identifying faulty conditions of devices behind a receive antenna such as typical microwave amplifiers. This method can be used during amplifier production to quickly identify and isolate faulty device production.